1993
DOI: 10.1159/000126346
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the Anterior Pituitary Gland of the Rat: Studies with Estrogen and Bromocriptine

Abstract: Apoptosis was investigated by electron and light microscopy in the anterior pituitary gland of the male Fischer rat in which hyperplasia of prolactin-secreting cells had been induced by estrogen implanted subcutaneously for 6 weeks. Counts by light microscopy of apoptotic cells and cells containing phagocytosed apoptotic bodies increased during a period of 44 h after estrogen withdrawal. Necrosis was present but was not prominent. Administration of bromocriptine after estrogen withdrawal increased apoptotic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 21 publications
2
43
0
1
Order By: Relevance
“…Similar structures have been reported by VILA-PORCILE (1973), who suggested that these heterogeneous substances might be the products of the phagocytosis of degenerated glandular cells which have accumulated as residual bodies within the colloid. This interpretation is supported by DREWETT et al (1993), who reported that FS cells phagocytosed apoptotic prolactin cells which appear after the suspension of estrogen treatment, or which appear after the administration of dopamine agonists such as bromocriptine.…”
Section: Electron Microscopic Observationsmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar structures have been reported by VILA-PORCILE (1973), who suggested that these heterogeneous substances might be the products of the phagocytosis of degenerated glandular cells which have accumulated as residual bodies within the colloid. This interpretation is supported by DREWETT et al (1993), who reported that FS cells phagocytosed apoptotic prolactin cells which appear after the suspension of estrogen treatment, or which appear after the administration of dopamine agonists such as bromocriptine.…”
Section: Electron Microscopic Observationsmentioning
confidence: 66%
“…First, the abundance of lysosomes within them suggests that they may act as scavenger cells (DINGEMANS and FELTKAMP, 1972;VILA-PORCILE,1973;STOKREEF et al, 1986). In this connection, their pronounced phagocytotic activity may have an important role in the removal of apoptotic cells (DREWETT et al, 1993). Secondly, FS cells are known to secrete several growth factors such as fibroblast growth factor (FGF) (FERRER et al, 1987), pituitary-derived vascular endothelial growth factor (PVEGF) (GSPODAROWIC and LAU,1987), follistatin and activin (KATAYAMA et al, 1992;KAISER et al, 1992) and interleukin-6 (IL-6) (VANKELCOM et al, 1989(VANKELCOM et al, , 1993.…”
mentioning
confidence: 99%
“…We observed only a small number of TUNEL-positive cells in each pituitary section while there were numerous Bax-immunoreactive cells. This marked difference may be accounted for by the fact that the apoptotic process has very rapid kinetics [7, 19, 29]and dead cells detected by the TUNEL method are rapidly eliminated by phagocytosis from the pituitary tissue by folliculostellate cells found abundantly in the anterior pituitary [9, 30]. Furthermore, it may be possible that high susceptibility to apoptosis as evidenced by Bax expression does not necessarily commit all Bax-immunoreactive cells to apoptotic cell death and only a proportion of the Bax-immunoreactive cells actually undergoes apoptosis in response to apoptotic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with animal models have provided some insights into the effects of hormones, particularly ovarian steroids, on cell death of pituitary cells. Drewett et al [9]reported that estrogen withdrawal increases apoptotic cell numbers in the anterior pituitary gland in estrogen-treated rats. This effect is further enhanced by treatment with the dopaminergic agonist bromocriptine.…”
Section: Introductionmentioning
confidence: 99%
“…However to our knowledge the expression of OX6 or other dendritic markers has not been investigated in TtT/GF cells. Ultrastructural studies in rat and guinea fowl have suggested a phagocytic role for F-S cells [111][112][113]. We are not aware of functional studies to support this and have been unable to demonstrate phagocytic activity by native F-S cells or TtT/GF cells, though the very slow turnover of endocrine cells may make this a rather rare event in the adenohypophysis.…”
Section: Communication With the Immune Systemmentioning
confidence: 90%